The Effect of Empowering Leadership on Innovation Behavior Mediated by Organizational Commitment in Six Basic Service Government Agencies Within the Provincial Government of North Maluku - Marliani Marliani; Abdullah W. Jabid; Sulfi Abdul Haji (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the influence of empowering leadership on innovation behavior mediated by organizational commitment in six basic service OPDs within the scope of the North Maluku Provincial Government. The research method uses a quantitative approach with Structural Equation Modeling analysis techniques based on Partial Least Square (SEM-PLS) using the SmartPLS 4.0 application. The research sample consisted of 137 ASN respondents in six basic service OPDs, including the Social Service, the Health Service, the Education and Culture Service, the Public Works and Spatial Planning Office, the Housing and Settlement Area Service, and the Pamong Praja Police Unit. The results showed that empowering leadership had a positive and significant effect on innovation behavior (t-statistic 2.805; p-value 0.005). Empowering leadership also has a positive and significant effect on organizational commitment (t-statistic 3.897; p-value 0.000). Organizational commitment has been proven to have a positive and significant effect on innovation behavior (t-statistic 5.517; p-value 0.000). Furthermore, organizational commitment significantly mediated the relationship between empowering leadership and innovation behavior (t-statistic 4.172; p-value 0.000). These findings make a theoretical and practical contribution to the development of leadership strategies in the public sector to improve the innovative behavior of employees through strengthening organizational commitment.